The most mysterious bookshop in Paris - Pryor, Mark, 1967- (A Paris bookshop mystery, 2026)
Hugo Marston, former head of security at the U.S. embassy in Paris, has retired and is ready to realize his lifelong dream of owning a mystery and antiquarian bookshop. But when a blackmail scheme targeting a chocolatier leads to murder, Hugo is again called to investigate in the first Paris Bookshop Mystery [...] Hugo has led an exciting life as an FBI profiler and the US embassy's head of security, but now he's ready to embrace a quieter existence as a bookseller in the Marais district of Paris. His former employer, however, has other plans for him. A prominent American citizen is the COO of a boutique chocolate emporium in Paris, where they've received a mysterious and threatening note. A blackmailer who goes by the name The Shadow wants half a million euros or else their "darkest secret will be revealed." Eclat de Chocolat is housed in a chateau dating back to the 1700s. The building, which served as a convent in the first half of the twentieth century, where the angelic Sister Evangeline and her order of nuns helped countless orphans during World War II, has been beautifully converted into a chocolate factory. So what dark secrets could a chocolatier be hiding? The COO has no idea. Involving his friend, Lieutenant Camille Lerens, Hugo begins to investigate. But soon a second note appears on the premises, canceling the blackmail threat. The same day, the body of an employee is found in an old graveyard behind the chocolatier. Now Hugo and Lerens have a murder on their hands, but is it connected to the blackmail attempt? As they dig for secrets and motives, it becomes clear The Shadow's grave work has just begun...